Directional correction of modeled sea and swell wave heights using satellite altimeter data. (November 2018) - Albuquerque, João; Antolínez, Jose A.A.; Rueda, Ana; Méndez, Fernando J.; Coco, Giovanni
Highlights: A correction for wave hindcasts based on satellite altimeter data is proposed. The technique corrects simultaneous sea and swell partitions present in a sea state. The proposed correction outperforms a similar technique applied for bulk sea states. The technique helped identifying systematic errors of the wave hindcast. The method could be applied worldwide to correct any partitioned hindcast. Abstract: This paper proposes a buoy independent directional calibration methodology that uses satellite altimeter data to correct the simultaneous wind-sea and all swell partitions available from wave hindcasts. The proposed technique was applied to a 20-year wave hindcast in the New Zealand region and showed promising results. The method could potentially be applied worldwide to fully assess systematic errors in wind-sea and swell partitions.